2006
DOI: 10.1038/sj.ejcn.1602393
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected changes in blood pressure and hematological parameters among fasting and nonfasting workers during Ramadan in Indonesia

Abstract: Objective: To examine the effect of Ramadan fasting on basic hematological parameters, in addition to the effects on body weight and blood pressure of fasters and nonfasters. Design, setting, and subjects: One hundred male outdoor workers at a vehicle terminal in a city in East Java were recruited for this study. Anthropometric measurements and blood sampling were conducted on two separate occasions, just before the start of Ramadan and in the third week of the month of Ramadan (October-November 2004). The deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 19 publications
(20 reference statements)
5
40
0
Order By: Relevance
“…In agreement with previous studies [18–20, 27, 28], our study indicated a significant reduction in body weight during Ramadan. This weight loss could be attributed to the decrease in fat mass% [27] and/or the decrease in fluid intake and the partial dehydration rather than a decrease in energy intake since weight loss was relatively small and retained to baseline values after Ramadan [20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies [18–20, 27, 28], our study indicated a significant reduction in body weight during Ramadan. This weight loss could be attributed to the decrease in fat mass% [27] and/or the decrease in fluid intake and the partial dehydration rather than a decrease in energy intake since weight loss was relatively small and retained to baseline values after Ramadan [20].…”
Section: Discussionsupporting
confidence: 93%
“…These mechanisms favor a predominant lipolytic state [15], with a higher tendency to utilize fat rather than glucose as a source of energy [19], and hence a higher fat oxidation. The increased fat oxidation during Ramadan was also reported previously [15, 19, 28]. …”
Section: Discussionsupporting
confidence: 86%
“…Despite the fact that these dietary guidelines have been in use for more than 1,700 years and have been described in numerous publications and languages, their potential implications for health have only recently (after the year 2002) begun to be investigated; unlike adherents of Christian dogmas and religions, such as the Seventhday Adventists (Willett 2003), Muslims and Buddhists for which the relevant literature is abundant (Frost and Pirani 1987;Temizhan et al 2000;Dewanti et al 2006;Lee and Krawinkel 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Studies conducted on the effects of Ramadan fasting on energy metabolism indicated increased fat oxidation [3] and reduced metabolism [7] in fasting subjects. Some hematological studies concluded that responses to different aggregating agents were reduced, resulting in increased bleeding and coagulation time [8] , and that red blood cell production is suppressed [9] during Ramadan. Hormonal studies showed altered cortisol levels [10] and endocrine and neuroendocrine circadian patterns [11,12] .…”
Section: Introductionmentioning
confidence: 99%